2023
DOI: 10.1002/ajpa.24696
|View full text |Cite
|
Sign up to set email alerts
|

Linking the proximal tibiofibular joint to hominid locomotion: A morphometric study of extant species

Abstract: ObjectivesWe perform a comparative assessment of shape variation of the proximal fibula in extant humans and great apes, intending to investigate the possible link between proximal fibular shape and locomotor patterns.MethodsOur sample includes 94 fibulae of 37 Homo sapiens, 15 Gorilla, 17 Pongo, and 25 Pan. Fibular morphology was investigated through three‐dimensional (semi)landmark‐based geometric morphometric methods.ResultsWe found unique features of the human fibular head compared to that of great apes (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Our work is aimed at investigating the entheseal morphometric variability of the femoral insertion of gluteus maximus (hereinafter "GM") and tibial origin of soleus (hereinafter "SOL") muscles (already studied in the Neanderthal samples) in juvenile individuals in relation to age, sex and locomotor pattern during growth, adding new insights on the biological and biomechanical aspects of bipedalism, from an ontogenetic and evolutionary point of view, already explored in our research group also with other approaches (Sorrentino et al, 2020a, 2020b, 2020c, Figus et al, 2022Pietrobelli et al, 2022aPietrobelli et al, , 2022bPietrobelli et al, , 2023Colombo et al, 2019). In detail, we developed a recording standard method to better classify the entheseal (continuous) variability into discrete classes and verify its applicability in response to the locomotor pattern (detailed below).…”
Section: Introductionmentioning
confidence: 99%
“…Our work is aimed at investigating the entheseal morphometric variability of the femoral insertion of gluteus maximus (hereinafter "GM") and tibial origin of soleus (hereinafter "SOL") muscles (already studied in the Neanderthal samples) in juvenile individuals in relation to age, sex and locomotor pattern during growth, adding new insights on the biological and biomechanical aspects of bipedalism, from an ontogenetic and evolutionary point of view, already explored in our research group also with other approaches (Sorrentino et al, 2020a, 2020b, 2020c, Figus et al, 2022Pietrobelli et al, 2022aPietrobelli et al, , 2022bPietrobelli et al, , 2023Colombo et al, 2019). In detail, we developed a recording standard method to better classify the entheseal (continuous) variability into discrete classes and verify its applicability in response to the locomotor pattern (detailed below).…”
Section: Introductionmentioning
confidence: 99%
“…In Homo sapiens and primates, the degree of mobility of the bula has been related to the degree of eversion/inversion and dorsi exion/plantar exion at the ankle joint (Marchi et al 2007). Recent 3D geometric morphometric (3D-GM) studies revealed that proximal and distal bular morphology are indicators of locomotor patterns associated with each extant hominid taxon (Marchi et al 2022;Pietrobelli et al 2023). The authors documented for proximal epiphysis a horizontal proximal tibio bular joint (PTFJ), a superiorly at bular head, an anterolateral and inferior expansion of hamstring and peroneal muscles insertions area onto the bular head, and a de ned but shallower, more medially expanded m. soleus insertion in great apes compared to humans.…”
Section: Introductionmentioning
confidence: 99%